Development and Testing of a Portable Air Purifier with Chemical and UV-C Filtration for Virus and Pollutant Removal - Yunita, Ailsa Rahma; Vegasty, Sabella; Izati, Zhahira Nur; Massardi, Adhie; Kusumaningsih, Triana; Firdaus, Maulidan (Universitas Andalas, 2025)
COVID-19 has profoundly impacted global health due to its severe respiratory effects. Similarly, respiratory issues are also triggered by pollutants such as O3, SO2, NO2, and CO. In response to these challenges, this study developed a portable air purifier called APMIKAV, incorporating sodium lauryl sulfate, activated carbon, and UV-C light as filter components. APMIKAV fabrication aimed to build a portable air purifier and study its effectiveness in filtering air containing viruses and pollutants into clean air. The APMIKAV utilized a three-stage filtration process that included a surfactant filter for pollutant removal and virus lysis, an activated carbon filter for pollutant adsorption, and a UV-C filter to deactivate viral DNA and RNA. Methods included designing, assembling, and testing. Antiviral testing was carried out with GeNose C19 on patients who tested positive for COVID-19, while air parameters were analyzed using an NDIR analyzer for CO and an air sampling impinger for O3, SO2, and NO2. Test with GeNose C19 showed negative results. Pollutant concentrations post-filtration average efficiency were 98.17%, 68.84%, 49.29%, and 66.34%, for NO2, O3, SO2, and CO, respectively. Overall, the multi-stage filtration process provided a robust solution for enhancing air quality in environments susceptible to both pollution and viral transmission, which confirmed APMIKAV's effectiveness in providing cleaner and safer air.